2013
DOI: 10.1038/pcan.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the frequency and duration of PSA measurement on PSA doubling time calculations in men with biochemically recurrent prostate cancer

Abstract: Background Prostate specific antigen (PSA) doubling time (PSADT) is an attractive intermediate endpoint for assessing novel therapies in biochemically recurrent prostate cancer (BRPC). This study explores whether PSADT calculations are influenced by frequency/duration of PSA measurements, and whether statistical variability leads investigators to find false significant results. Methods In retrospective analyses of two BRPC cohorts: Johns Hopkins Hospital (JHH) patients who deferred therapy and placebo patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…12 Recently, is has been suggested that PSADT changes of this magnitude can be explained by natural variation in PSADT in patients with biochemically recurrent prostate cancer. 37 Paller et al 37 have recently shown in a retrospective study that PSA variability in such men can lead to a natural lengthening of PSADT over time, and they suggest that increase in PSADT of 6 months or less, even when statistically significant, are unlikely to be clinically meaningful in the absence of a placebo control and their use to be interpreted with caution in uncontrolled single-arm studies. Recently, Antonarakis et al 38 preformed a hypothesis-generating retrospective analysis of 4 phase II trials that suggests that within- subject changes in PSADT and PSA slope after initiation of experimental therapy may correlate with metastasis-free survival in men with biochemically recurrent prostate cancer, though their findings require prospective validation.…”
Section: Discussionmentioning
confidence: 97%
“…12 Recently, is has been suggested that PSADT changes of this magnitude can be explained by natural variation in PSADT in patients with biochemically recurrent prostate cancer. 37 Paller et al 37 have recently shown in a retrospective study that PSA variability in such men can lead to a natural lengthening of PSADT over time, and they suggest that increase in PSADT of 6 months or less, even when statistically significant, are unlikely to be clinically meaningful in the absence of a placebo control and their use to be interpreted with caution in uncontrolled single-arm studies. Recently, Antonarakis et al 38 preformed a hypothesis-generating retrospective analysis of 4 phase II trials that suggests that within- subject changes in PSADT and PSA slope after initiation of experimental therapy may correlate with metastasis-free survival in men with biochemically recurrent prostate cancer, though their findings require prospective validation.…”
Section: Discussionmentioning
confidence: 97%
“…The use of PSA dynamics (such as PSADT, PSA slope, PSA velocity) is of unestablished clinical significance, and is often highly variable as observed even on placebo arms of trials. 54 In addition, the impact of modulating PSA kinetics on clinically defined endpoints (such as metastasis-free survival) remains uncertain. 55 …”
Section: Drug Development Endpoints For Biochemically-recurrent Prostmentioning
confidence: 99%
“…7 For trials involving patients with biochemical recurrence to provide clinically meaningful results, far more information is needed on the natural history and variation of PSADT in that patient population. 54 Despite these challenges, trials in this patient population can provide important information on drug activity, pharmacokinetics and pharmacodynamics.…”
Section: Drug Development Endpoints For Biochemically-recurrent Prostmentioning
confidence: 99%
“…Additionally, in this study, PSADT was not associated with salvage failure, although it has been reported as a determinant for systemic disease in recurrent prostate cancer [27]. In a previous study, PSADT was reported to be influenced by the duration of PSA follow-up before initiation of salvage treatment because PSADT increased over time if treatment was not performed for recurrent disease [28]. In other words, presalvage PSA level, which is related to the timing of salvage treatment, could be more important for predicting oncological outcomes than PSA kinetics, including PSADT.…”
Section: Discussionmentioning
confidence: 78%